1987
DOI: 10.1111/j.1476-5381.1987.tb08987.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide is localised to human airway nerves and potently constricts human airway smooth muscle

Abstract: 1 In human airways synthetic human sequence calcitonin gene-related peptide (hCGRP), a novel peptide produced by alternative processing of mRNA from the calcitonin gene, caused concentrationdependent contraction of human bronchi (EC_, 4.9 x 10-' M) and was significantly more potent than substance P or carbachol. 3 CGRP was detected in human airways by radioimmunoassay with highest concentrations in cartilaginous airways. 4 CGRP was localised by immunocytochemistry to both nerves and ganglia in human airways. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(40 citation statements)
references
References 22 publications
2
37
0
1
Order By: Relevance
“…In agreement with Malm & Petersson (1985) we have not observed any effect of topical SP at a dose capable of inducing facial flushing. Nerve fibres, containing CGRP, have recently been shown in the human airways (Palmer et al, 1987). Functional evidence has been presented indicating that CGRP may be responsible for many acute responses to capsaicin which cannot be ascribed to SP (Franco-Cereceda & Lundberg, 1985;Hua & Lundberg, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Malm & Petersson (1985) we have not observed any effect of topical SP at a dose capable of inducing facial flushing. Nerve fibres, containing CGRP, have recently been shown in the human airways (Palmer et al, 1987). Functional evidence has been presented indicating that CGRP may be responsible for many acute responses to capsaicin which cannot be ascribed to SP (Franco-Cereceda & Lundberg, 1985;Hua & Lundberg, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…SP and two newer members of the tachykinin family, neurokinin A (NKA) and neurokinin B (NKB) have been shown to increase vascular permeability in guinea-pig trachea (Lundberg et al, 1985) although, of the two neurokinins, only NKA has been localized to capsaisin-sensitive nerves in the guinea-pig (Hua et al, 1985a). Recently, calcitonin gene-related peptide (CGRP) has been localized to airway nerves in rat (Cadieux et al, 1986;Lauweryns & Van Rast, 1987) and man (Palmer et al, 1987 Lundberg et at., 1985;Gulbenkian et al, 1986). CGRP exhibits potent vasodilator activity but, unlike the tachykinins, does not increase vascular permeability in guinea-pig trachea (Lundberg et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of bradykinin may be due to release of sensory neuropeptides such as calcitonin gene-related peptide and the tachykinins substance P and neurokinin A, which have been localised to airways in animals and man (Lundberg et al, 1984;Polak & Bloom, 1982;Martling et al, 1987;Ueda et al, 1984) and have been shown to have potent bronchoconstrictor actions in human airways (Martling et al, 1987;Barnes, 1987;Joos et al, 1987;Palmer et al, 1987;Evans et al, 1988). Thus bradykinin may release sensory neuropeptides as part of an axon reflex (Barnes, 1986), and it is possible that sodium cromoglycate and nedocromil sodium interfere with this response.…”
Section: Discussionmentioning
confidence: 99%